Artificial Intelligence (AI) Integration Training and Mentoring in Productive Curriculum Development at Ilhami Kemiri Vocational School, Tangerang Regency - Muhammad Syukri; Bambang Suhartono; Murinto Murinto; Herman Herman (Jurnal Pengabdian Masyarakat: Bisnis dan Iptek (JPMBISTEK), 2026)
The swift advancement of Artificial Intelligence (AI) technology requires vocational education institutions to revise their curricula to meet the demands of the digital industry. This study examines the implementation of training and mentorship for AI integration in the development of productive curricula at SMK Ilhami Kemiri, Tangerang Regency, while assessing teachers' understanding and preparedness to incorporate AI into the educational process. The researcher utilized a mixed-methods approach consisting of a systematic sequence of stages: identifying training needs, developing materials and instruments, conducting training sessions, facilitating AI integration, gathering questionnaire data, and executing both quantitative and qualitative analyses. Data were collected from effective subject teachers, who served as the principal participants. The findings indicate that the training significantly improves teachers' foundational understanding of AI ideas and applications in education. At the same time, mentorship is crucial for helping instructors implement AI in instructional tools and classroom practices. Data analysis reveals a rise in perceived teacher preparedness, especially in the application of AI for material creation, learning assessment, and effective curriculum improvement. This research advocates for the implementation of sustainable training programs, enhanced digital infrastructure support, and the creation of an integrated AI-based competency curriculum to facilitate the transition of vocational education at the Vocational High School level.